PENGEMBANGAN USAHA VOKASI MELALUI PEMANFAATAN POTENSI DESA WADO - Moh Yamin Darsyah; Rochdi Wasono; Iswahyudi Joko Suprayitno; Iis Istiqomah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Wado is a village that has great potential that still needs development. This area is a peanut producing area. The majority of people in Wado sell abundant peanuts every harvest is only sold to middlemen, not much use of peanuts to be processed into high-value peanut production. This resulted in the potential of peanut in Wado has not contributed the maximum to the welfare of the community. The purpose of KKN-PPM is toprovide knowledge to the Wado Village community to empower themselves through peanut business, to provide process processing skills and peanut packing process as typical food of Kedungtuban village, to  provide knowledge and skills of marketing process of peanut products widely, to provide assistance in the learning activities of school-aged children and to provide assistance to the Wado Village community in processing peanuts into typical food products and regional superior. Methods used to solve problems include using lecture strategies, observation, discussion, case studies, demonstrations, practices and brainstorming suggestions. The result of this activity is the change of mindset of the community to consciously process the local potential of the village to be a product of sale value in Wado Village, Kedungtuban Sub-district of Blora Regency, the product produced by KKN-PPM in the form of peanut stick, peanut cruncy 3G, peanut butter, chicken peanut nugget, milk peanut powder and ketapang seeds rich in flavor. This processed peanut products can be sold widely through online and have filed No.PIRT products. In addition, other activities in the field of education, environment and health have been done to provide awareness for the community so that there is a change in public attitudes to be more concerned about education, environment and health.